International commercial agreements : an Edinburgh law guide - Meiselles, Michala (Edinburgh University Press, 2013)
A key reference tool for business managers, lawyers and students, this accessible book covers the essential issues that need to be dealt with when negotiating, planning and writing international commercial agreements. It looks at the issues that must be taken into account when a business located in one country is contracting with a business located in another country, exploring the framework within which such international commercial agreements are concluded.